P967Role of low voltage ablation in catheter ablation of patients with persistent AF- a single centre experience. (18th June 2020) - Panagopoulos, D; Nagy, S; Kim, S; Lampridou, M; Linton, N; Lefroy, D; Whinnett, Z; Ng, F S; Koa-Wing, M; Kanagaratnam, P; Peters, N S; Qureshi, N; et al.
Abstract: Funding Acknowledgements: Research grant from Abbott Introduction: We have recently described a novel evaluation of AF voltage which correlates better with MRI-DE defined scar than sinus rhythm voltage. We evaluated the clinical efficacy of additional voltage-based substrate modification in the Persistent AF patient cohort in a single centre case series. Methods 22 PsAF patients undergoing catheter ablation were recruited. Left atrial electroanatomical maps were created in AF before any ablation was performed in all patients. Mean peak to peak AF voltage mapping was undertaken using 8s segments of AF (<0.35mV).  PVI was then performed in all patients after which, further ablation lesions were delivered on the underlying scar tissue (transection, box formation or homogenisation). Results: Of the 22 patients currently under follow up, 16 patients are more than 12 months after their initial procedure. 11/16 patients have had no recurrence and no patient is currently on anti-arrhythmic medication. Conclusion: From our series, 69% of PsAF patients remain arrhythmia free at one year follow up post blanking period with a single procedure. Ablation of low voltage areas appears to infer incremental benefit in the Persistent AF population.